Effect of urea fertilizer on soil, plant and food grain - Bari, Md. Niamul; Alam, Md. Zahangir; Sharmin, F J; Rashid, Md. Harunur (2007)
The use of nitrogen fertilizer as a source of nitrogen for the growth of plant is very common in Bangladesh even all over the world. In fact the inherent supplies of readily available nutrients for Bangladesh soil are limited. The crops absorb nutrients from these insufficient supplies and the soil become exhausted. So, soil needs additional chemical fertilizers for supporting the growth and development of crops. However the accumulation pattern, recovery and losses of added chemicals in soils are of great concern in environmental pollution. A thorough investigation of accumulation of nitrogen fertilizer in soil and food-chain as well as plant has been carried out for rice crop. The soil and crop samples are collected from Bangladesh Rice Resources Institute, Rajshahi at different times of fertilization from different locations and depths. The analytical analysis for nitrogen content is carried out at environmental laboratory of Rajshahi University of Engineering and Technology. The result shows that the concentration of nitrogen in soil, plant (root, stem and leaf) and grain is much higher than the allowable limit which may create serious environmental problem and tremendous health hazard for human as well as animal.